Comparison of Inhibitory Control Skill in 6 to 8-Year-Old Children With Fluent Speech and Developmental Stuttering - Atefeh Rahmati (Journal of Modern Rehabilitation, 2019)
Introduction: Fluent speech requires inhibitory control for the modification of speech interruptions before the onset or during the speech. The current study aimed at comparing the inhibitory control skill in 6 to 8-year-old children with fluent speech and developmental stuttering. Materials and Methods: This research is a descriptive-analytic cross-sectional study. The participants included 31 children with developmental stuttering (6-8 years old) selected based on the convenience sampling method. Also, 32 healthy children were selected from elementary schools in Tehran Province that matched in terms of age and gender with the first group. The children of two groups were selected from the same district (The fifth district) of Tehran Province. Visual Go/No-Go task was used to measure inhibitory control. The Mann-Whitney U test was used to compare the groups. Results: The result showed that the mean score of children with stuttering in the inhibition index was lower than normal children. According to the Kolmogorov-Smirnov test, the data distribution was not normal (P=0.042). Therefore, the parametric test of the Mann-Whitney U test was used. Despite the lower mean score of inhibition in children with stuttering than healthy children, there was no significant difference in the inhibition index between the groups (P=0.550). Conclusion: The findings indicated that Children Who Stutter (CWS) had less efficiency in inhibitory control skill compared to normal children, and this problem could be because of the exacerbation or persistence of stuttering.